KUALITAS DAN KENYAMANAN UDARA PADA GEDUNG PERKANTORAN BERTINGKAT RENDAH DENGAN STUDI KASUS GEDUNG PERKANTORAN PT. X DI JAKARTA - Putri Nur Ratnasari; Dyah Nurwidyaningrum (Construction and Material Journal, 2020)
Green Building Council Indonesia (GBCI) publishes an assessment device called Greenship to be used as a benchmark in planning to maintain green buildings. PT. Medtek one of the low-rise office buildings in Jakarta that is an area with moderate air pollution level based on air Pollution Standard Index (ISPU) which has no effect on human or animal health but influential on sensitive plants and aesthetic values. This research aimed to know the criteria points obtained by PT. Medtek,  influence of air quality, and building conditions in the user of the building.  Measurements of indoor air health, comfort and questionnaire data collection is done indoors when user’s activity in an office building is underway. The method used is a comparison method by comparing the results of field measurements with Greenship Rating Tools Existing Building version 1.1. The criteria achieved by PT. Medtek are a non-smoking campaign, outside air introduction, cigarette smoke control, and visual comfort. Criterion points earned 12 out of 18 scoring points are reviewed or meet 66.67% of the total assessment aspect of quality and comfort of indoor air. Keywords: Green Building, Greenship, Air Pollution, Air Quality, Low-Rise Office.